The Hermeneutic of the Malay Comic: Unveiling the Symbolism of Love in Selendang Siti Rugayah - Julina Ismail@Kamal,; Md. Salleh Yaapar, (Wacana Seni Journal of Arts Discourse, 2020)
A comic is a form of sequential art that incorporates the integrated textual and visual aspects to reveal the desired meaning. It involves storytelling techniques with narrative elements as found in conventional literary works. Nowadays, comic art is flourishing in Malaysia with the advent of abundant comics from various old and new local authors. The uniqueness of Rejabhad, who was widely known as the King of Malaysian Cartoon, allows the researcher to analyse his comic works in the aspects of textual and visual designs. Prior studies have only discussed the outer layer of Malay comics. In fact, Malay comics especially Rejabhad’s works need to be examined more deeply to unravel their outer and inner layers of meaning. It is essential to fully understand the overall meaning of the work as well as to appreciate the author’s identity. This study focuses on one of Rejabhad’s particular comic work entitled “Selendang Siti Rugayah” (1997). The study uses a spiritual hermeneutic reading or exegesis (takwil) method is applied to obtain the inner or spiritual meaning of “Selendang Siti Rugayah” comic work. The results of this study allow the public to understand the inner meaning of the comic work and to appreciate the identity or personality of the author in his or her comic works. This study which based on the spiritual hermeneutic reading is very significant. It is a new exploration that may change the views on the creativity and wisdom of a Malay comic artist, Rejabhad, who had been appreciated and understood only based on the outer layer of reading.